2009
DOI: 10.1007/s00106-008-1777-z
|View full text |Cite
|
Sign up to set email alerts
|

Is postoperative antibiotic treatment mandatory after abscess tonsillectomy

Abstract: We conclude that immediately performed abscess tonsillectomy is an effective and safe treatment for PTA. No higher complication rate was found when additional antibiotic treatment was not used. Because of the small number of cases, the results can be regarded only as a tendency, not as a general recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is possible that the simple act of draining the abscess is effective treatment and that antibiotic therapy may not be necessary. A German study investigated this prospectively in abscesses treated with tonsillectomy and found no difference between the treatment and control groups [8]. Generalizing these findings to needle drainage is likely not valid, but does provide further evidence that definitive drainage of the abscess may well be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the simple act of draining the abscess is effective treatment and that antibiotic therapy may not be necessary. A German study investigated this prospectively in abscesses treated with tonsillectomy and found no difference between the treatment and control groups [8]. Generalizing these findings to needle drainage is likely not valid, but does provide further evidence that definitive drainage of the abscess may well be sufficient.…”
Section: Discussionmentioning
confidence: 99%